1989
DOI: 10.3171/jns.1989.71.4.0605
|View full text |Cite
|
Sign up to set email alerts
|

Delayed postoperative neurological deterioration from prolonged sodium nitroprusside administration

Abstract: Sodium nitroprusside is commonly used for the induction of hypotension during neurosurgical procedures. Its toxicity stems from hemodynamic compromise as well as from its metabolites, especially the formation of cyanide. A patient is described who underwent craniotomy for hypertensive intracerebral hemorrhage. He gradually recovered following the operation, but needed continued administration of sodium nitroprusside for control of hypertension. On the 7th postoperative day, he deteriorated into coma with evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…But its effectiveness needs to be confirmed clinically. Furthermore, the longterm therapy (2-3 weeks) with SNAP resulted in cyanide toxicity 80 . We have also tried intravenous delivery of a newly developed NO donor 82 , which spontaneously releases NO and has an extremely short half life (1.8 seconds).…”
Section: No Delivery: Systemicmentioning
confidence: 99%
“…But its effectiveness needs to be confirmed clinically. Furthermore, the longterm therapy (2-3 weeks) with SNAP resulted in cyanide toxicity 80 . We have also tried intravenous delivery of a newly developed NO donor 82 , which spontaneously releases NO and has an extremely short half life (1.8 seconds).…”
Section: No Delivery: Systemicmentioning
confidence: 99%
“…When used clinically to treat emergency hypertension, sodium nitroprusside sometimes causes delayed neurodegeneration (Kim et al, 1982;Ram et al, 1989), which may be related to the toxicity observed in cultured cerebellar granule neurons treated with nitroprusside as shown in this study. The mechanisms underlying sodium nitroprusside neurotoxicity are complex, possibly involving lowering of [Ca 2~], (present study), inhibition of excitatory amino acidinduced phosphoinositide hydrolysis (Yu and Chuang, 1995), NO cascade (Dawson et al, 1991;Gross, 1995), and/or the actions of the breakdown products of sodium nitroprusside such as cyanide and iron.…”
Section: Rescuing Effects On Neurons By Neurotrophinsmentioning
confidence: 57%
“…23) However, the feasibility of continuous use remains unclear, as cyanide poisoning and cyanide encephalopathy are possible, even at low doses. 21) Higher doses of intravenous nitroglycerin are necessary for the treatment of cerebral vasospasm, which may affect mean arterial pressure. 2,12) Moreover, thiols are essential for the biotransformation of nitroglycerin or other nitrates to generate NO, so depletion of thiols results in development of tolerance.…”
Section: Discussionmentioning
confidence: 99%